Towards multiple operating point axial fan design - Semel, Matthias; Haag, Viktor; Delgado, Antonio; Grilliat, Julien (ASME Turbo Expo 2015: Turbine Technical Conference and Exposition, 2015)
The dimensionless performances of an axial fan are derived analytically from an arbitrary work distribution. The formulation is illustrated using five different work distributions at a selected operating point and comparing the resulting hydraulic characteristics. A first validation of the formulation is brought by means of RANS and URANS of an axial fan with free vortex work distribution. It is shown that a single RANS prediction at the design point allows predicting the hydraulic characteristic up to 20% off the design flow rate with very good accuracy. Based on these results, a strategy for axial fan design at multiple operating points is propose
UnivIS-Import:2016-06-01:Pub.2015.tech.ITC.stmmec.toward